A DESCRIPTIVE STUDY ON THE PROBLEMS IN READING COMPREHENSION OF THE ELEVENTH GRADE OF STUDENTS OF SMA NEGERI 6 BANJARMASIN - Yazirwan Mahyuddin Mahyuddin (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
Reading is one of four skills that is learned school. Reading is a process of how we find information from what we see. Like the other skills, reading comprehension is not easy. Students often face many problems in reading comprehension because of their limited ability and vocabulary in understanding readings materials. The researcher interested in students problems in reading comprehension of eleventh grade of SMA Negeri 6 Banjarmasin in Academic year 2017/2018. The objective of study is to describe the problems faced by the students of eleventh grade of SMA Negeri 6 Banjarmasin in reading comprehension. The researcher used descriptive quantitative research as the type of research. The population of the research was 253 and the sample was 71 students. The technique sampling is cluster random sampling. The instruments used were test-retest and questionnaire. Based on the research result, the students had two problems. There are finding main idea and guessing meaning from context. The mayor problem is guessing meaning form context and the minor problem is finding the main idea. From questionnaire, students had a problem in finding main idea and guessing meaning from context.  Finally, it is suggested that for English teacher to improve reading skills and improve student’s vocabulary, word meaning, and knowledge about main idea in reading by providing more exercises in reading comprehension and active to find the meaning of the word that they found. The students should read English text not only in school but also read in outside school.